Archival Harm Reduction: A Theoretical Framework for Utilizing Harm-Reduction Concepts in Archival Practice - Payne, Krystal (Archivaria)

(untitled) (Association of Canadian Archivists, 2022)
Canadian archives arose from and help maintain white supremacist and settler-colonial frameworks. The inequitable power relations that exist in archives and archival practices contribute to the harms done to Indigenous people and communities; they do so through the ongoing entrenchment of settler colonialism and the participation in extractive colonialism that occur within the processes of archiving and through the systemic racism that comes along with these processes. This article lays out the beginnings of a theoretical framework for an archival harm-reduction approach for managing records by, about, and for Indigenous people and communities that are held in settler archival institutions and managed by settler archivists. Built upon an explicit acknowledgement of the harm that can occur within archives and through archival practices, and connecting public health harm-reduction concepts with Indigenous scholars’ ideas around relationality and power, this framework conceptualizes a process for shifting archival power by building relationships to ensure that the people and communities that records are about or from whom records originate are meaningfully involved in the stewardship of such records. The core harm- reduction concept of involving people and communities as the experts in their own lives (and records) is extended to archival practice – touching on topics such as consent, agency, autonomy, and social justice as well as on practices that are community-based, participatory, and reparative – helping to further articulate a person-centred archival theory and practice and illuminating the fact that settler archives cannot simply redescribe their way out of white supremacy.